If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 = 1 + -5n + -6n Combine like terms: -5n + -6n = -11n 12 = 1 + -11n Solving 12 = 1 + -11n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '11n' to each side of the equation. 12 + 11n = 1 + -11n + 11n Combine like terms: -11n + 11n = 0 12 + 11n = 1 + 0 12 + 11n = 1 Add '-12' to each side of the equation. 12 + -12 + 11n = 1 + -12 Combine like terms: 12 + -12 = 0 0 + 11n = 1 + -12 11n = 1 + -12 Combine like terms: 1 + -12 = -11 11n = -11 Divide each side by '11'. n = -1 Simplifying n = -1
| x-3x+620=2928 | | -3m+10=25 | | X+7=-3x+51 | | -16=4+5r+5r | | 3(1.5)-1/4(1.5)+2 | | x-3x+530=2994 | | 15y^2+7y-2=0 | | 10+6n=2(1-n) | | 6d/5=6d-96 | | -4.9x^2+24x+3=25 | | -10d-3= | | 7-3(x-4)=2(4x+1) | | 14r^2-21r=0 | | 8(m-2)=32 | | v+4+3=11 | | 5ln(8x)=20 | | -4.9x^2+24t+3=25 | | 14r^2-21=0 | | 3.7/m=-8 | | -5+5x=4x+0 | | -x-2=3x+2 | | 11z^2-44=0 | | 3b-2b=1 | | -4.9x^2+24x-22=0 | | x^4+x^2=5 | | x+3x+15=123 | | -56=8(1-8x) | | (3y^2-3y+2)+(4y^2+3y-1)=0 | | 5c/3=3c-32 | | 3x+y+5=13y-2x | | 105=16q-q | | 8x-(0.2)=9.8 |